(untitled) (Ghana Journal of Science, Technology and Development, 2022)
Turmeric (Curcuma longa L.) is one of the spices commonly used globally due to its health-promoting properties. The rhizomes are however perishable due to their high water content. In this study, the effect of different pretreatments and drying methods, viz. hot air drying (HAD) at 60 ℃ and forced air solar drying (FASD), on the drying kinetics, water activity, color, ß-carotene, and vitamin C contents of turmeric rhizomes were investigated. Prior to the experiments, fresh turmeric rhizomes were sliced into 3 mm thickness and treated either by steam blanching or immersion in an ascorbic acid solution. The untreated samples served as a control. The results showed that blanching and ascorbic acid treatments decreased the drying time by 11% and 31% each under the HAD and 30% and 18% under FASD when compared with the control, respectively. The water activity of steam blanching, ascorbic acid, and control samples dried under HAD and FASD was below 0.60, which is sufficient to inhibit spoilage. Ascorbic acid pretreated samples dried under HAD, and FASD resulted in significantly (P<0.05) lower total color change (HAD=14.06; FASD=12.79) with greater retention for vitamin C (HAD: 895.67±1.76 mg/100g; FASD=858.73 mg/100g) contents. Beta-carotene content was, however, not altered (p> 0.05) by the pretreatment, drying method, and their interaction. In conclusion, pretreating turmeric rhizomes with the ascorbic acid solution before HAD at 60°C will be ideal for preserving the color properties, vitamin C and β-carotene contents.